All-d-Enantiomer of β-Amyloid Peptide Forms Ion Channels in Lipid Bilayers - Capone, Ricardo (American Chemical Society, 2012)
Alzheimer’s disease (AD) is the most common type of senile dementia in aging populations. Amyloid β (Aβ)-mediated dysregulation of ionic homeostasis is the prevailing underlying mechanism leading to synaptic degeneration and neuronal death. Aβ-dependent ionic dysregulation most likely occurs either directly via unregulated ionic transport through the membrane or indirectly via Aβ binding to cell membrane receptors and subsequent opening of existing ion channels or transporters. Receptor binding is expected to involve a high degree of stereospecificity. Here, we investigated whether an Aβ peptide enantiomer, whose entire sequence consists of d-amino acids, can form ion-conducting channels; these channels can directly mediate Aβ effects even in the absence of receptor–peptide interactions. Using complementary approaches of planar lipid bilayer (PLB) electrophysiological recordings and molecular dynamics (MD) simulations, we show that the d-Aβ isomer exhibits ion conductance behavior in the bilayer indistinguishable from that described earlier for the l-Aβ isomer. The d isomer forms channel-like pores with heterogeneous ionic conductance similar to the l-Aβ isomer channels, and the d-isomer channel conductance is blocked by Zn(2+), a known blocker of l-Aβ isomer channels. MD simulations further verify formation of β-barrel-like Aβ channels with d- and l-isomers, illustrating that both d- and l-Aβ barrels can conduct cations. The calculated values of the single-channel conductance are approximately in the range of the experimental values. These findings are in agreement with amyloids forming Ca(2+) leaking, unregulated channels in AD, and suggest that Aβ toxicity is mediated through a receptor-independent, nonstereoselective mechanism.